2018
DOI: 10.21307/acee-2018-028
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Building Parameters and way of Operation on the Operative Temperature in Rooms

Abstract: Thermal environment in buildings is one of the most important aspects for occupants' comfort [1]. Thermal comfort, i.e. satisfaction with the environment depends on the occupants' thermal sensation. The thermal sensation is a function of four physical variables of indoor environment in the room (air temperature, mean radiant temperature, relative air humidity and air velocity) and two variables related to people (activity level and clothing). Knowledge of these parameters allow to predict the mean thermal sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…environments in accordance with the EN 16798-1:2019 standard [42], for which the operative temperature was 20 °C. The average difference between the air temperature and the operative temperature was assumed to be 1 K [54].…”
Section: Internal Heat Gainsmentioning
confidence: 99%
See 1 more Smart Citation
“…environments in accordance with the EN 16798-1:2019 standard [42], for which the operative temperature was 20 °C. The average difference between the air temperature and the operative temperature was assumed to be 1 K [54].…”
Section: Internal Heat Gainsmentioning
confidence: 99%
“…It was assumed that flats were 21 • C (whole day), staircases were 16 • C (whole day), and that basements had no heating. The assumption was made for category II thermal environments in accordance with the EN 16798-1:2019 standard [42], for which the operative temperature was 20 • C. The average difference between the air temperature and the operative temperature was assumed to be 1 K [54].…”
Section: Indoor Temperaturementioning
confidence: 99%
“…The value of the operative temperature differs from the indoor air temperature because it takes into account the thermal radiation of the surrounding building partitions. Research on this topic can be found in the work of Kaczmarczyk et al [47].…”
Section: Thermal Comfort Modelmentioning
confidence: 99%
“…As mentioned earlier in the adaptive model, the operative temperature occurred, while the cooling devices are controlled by the air temperature. In this study, according to the literature [47], it was assumed that the air temperature was 1.5 • C lower than the operative temperature. Instantaneous values of the air temperature set-point (theoretical comfort air temperature line) were calculated for the entire year as instantaneous operative temperature determined according to EN 16798-1:2019 [44] with the assumed offset.…”
Section: Case Studiesmentioning
confidence: 99%
“…The seasonal heat demand in buildings based on short measurement periods was presented in [28][29][30]. Indoor environmental conditions were analyzed focusing on the operative temperature and air quality [31,32]. The analysis of the building's insulation condition was examined in terms of determining seasonal heat consumption [33][34][35].…”
Section: Introductionmentioning
confidence: 99%